2015
DOI: 10.18311/mvpjms/2015/v2/i2/783
|View full text |Cite
|
Sign up to set email alerts
|

Study of Diagnostic Importance of Adenosine Deaminase (ADA) Level in Pleural Effusions

Abstract: Introduction: Pleural effusion is the abnormal accumulation of fluid in the pleural space. TB is the most common cause of pleural effusion worldwide (30-60%). The pleural fluid activity of adenosine deaminase (ADA) is one of the best, providing reliable basis for a treatment decision, particularly in excluding the diagnosis of tuberculosis, due to its high sensitivity1. Aims and Objectives: To assess the importance of adenosine deaminase(ADA) level in the diagnosis of pleural effusion. To assess Adenosine Deam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…29 In present study, the serum ADA activity was significantly increased (p<0.001) in pulmonary tuberculosis patients with pleural effusion when compared to healthy controls, transudative pleural effusion and exudative pleural effusion in conformance with study of Sonone et al 30 In present study, the pleural fluid ADA activity in pulmonary tuberculosis patients with pleural effusion was significantly increased (p<0.001) when compared to transudative and non-tuberculous exudative pleural effusion controls which was in agreement with Sonone et al, Devkota et al, Gupta BK et al, and Lee et al [30][31][32][33] The pleural fluid ADA level rarely exceeds the cut off limit of >40U/L in nontuberculous lymphocytic effusions. 34 In present study, the pleural fluid ADA levels were >40U/L in all 40 cases of pulmonary tuberculosis with pleural effusion. In present study, the pleural fluid ADA levels were significantly higher than serum ADA levels in pulmonary tuberculosis patients with pleural effusion (p <0.001) which was in conformance with studies of Sharma SK et al, and Piras et al 35,36 In present study, the serum ADA activity in treated pulmonary tuberculosis patients was significantly decreased (p<0.001) when compared to pulmonary tuberculosis patients, which was in conformance with Shibagaki T et al, indicating the role of pleural fluid ADA activity as prognostic marker of the disease.…”
Section: Discussionsupporting
confidence: 49%
“…29 In present study, the serum ADA activity was significantly increased (p<0.001) in pulmonary tuberculosis patients with pleural effusion when compared to healthy controls, transudative pleural effusion and exudative pleural effusion in conformance with study of Sonone et al 30 In present study, the pleural fluid ADA activity in pulmonary tuberculosis patients with pleural effusion was significantly increased (p<0.001) when compared to transudative and non-tuberculous exudative pleural effusion controls which was in agreement with Sonone et al, Devkota et al, Gupta BK et al, and Lee et al [30][31][32][33] The pleural fluid ADA level rarely exceeds the cut off limit of >40U/L in nontuberculous lymphocytic effusions. 34 In present study, the pleural fluid ADA levels were >40U/L in all 40 cases of pulmonary tuberculosis with pleural effusion. In present study, the pleural fluid ADA levels were significantly higher than serum ADA levels in pulmonary tuberculosis patients with pleural effusion (p <0.001) which was in conformance with studies of Sharma SK et al, and Piras et al 35,36 In present study, the serum ADA activity in treated pulmonary tuberculosis patients was significantly decreased (p<0.001) when compared to pulmonary tuberculosis patients, which was in conformance with Shibagaki T et al, indicating the role of pleural fluid ADA activity as prognostic marker of the disease.…”
Section: Discussionsupporting
confidence: 49%
“…7 2 mL of pleural fluid was collected in a sterile container and was either immediately analyzed or refrigerated at 4 • C and analyzed within two days. An ADA value >40IU/L was taken as a cut off value for diagnosing tubercular effusion 8,9 .…”
Section: Methodsmentioning
confidence: 99%
“…Sravan Kumar and Ritesh Agarwal study found poor utility, sensitivity as a diagnostic tool in diagnosing tuberculous and nontuberculous pleural effusion patients in chronic Kidney disease patients compared to DNA PCR. 9 Sachin Kate and B. K. Muthaa et al 10 in their study found a sensitivity and specificity of 93.3% and 90% respectively when ADA levels of 40 IU/L was taken as the criteria for the diagnosis of Tuberculous pleural effusion. Dr. Prabhakarra Rao et al 11 also found Pleural fluid ADA as a very sensitive and specific marker of tuberculous pleural effusion and is simple, inexpensive and rapid.…”
mentioning
confidence: 93%